Association of Diet Consumption with Gallbladder Changes in Females After Birth of Child: Diet Consumption with Gallbladder Changes - Abdul Razzak, Asma; Rahu, Sara Shafi; Usmani, Javeria (Pakistan Journal of Health Sciences, 2023)
The postpartum period is characterized by remarkable physiological adaptations to accommodate the demands of childbirth and lactation. These physiological changes, coupled with the unique nutritional needs of both the mother and newborn, can lead to gallbladder stasis and increased cholesterol absorption in the gallbladder. Objective: To assess the correlation between diet consumption and gallbladder changes in females after childbirth. Methods: This observational study was conducted at the department of Gastroenterology, Jinnah Medical and Dental College, Sohail University, Karachi, Pakistan from December 2022 to June 2022. Females of reproductive age who had normal child delivery were evaluated after 6 weeks of delivery. The medical examination, anthropometric measures, nutritional assessment, and laboratory testing were performed in all eligible females. An ultrasonographic was done after a typical fatty food in order to assess gallbladder changes. SPSS version 21.0 was used to do statistically analysis. Results: The mean age was 28.89 ± 4.73 and mean BMI was 22.78 ± 4.09 kg/m2. Of 100 females, 17% had gallbladder stasis, 26% had gallstones, and 17% had sludge. The females with low protein consumption had significantly higher proportion of gallbladder stasis as compared to females with high protein consumption in diet (76.5% vs 23.5%, p=0.001). Furthermore, females with high carbohydrate (61.5% vs 38.5%, p=0.011) and fructose (53.8% vs 46.2%, p=0.037) consumption had significantly higher proportion of gallstones as compared to females with low consumption. Conclusions: High protein consumption was linked to gallbladder stasis, while high carbohydrate and fructose intake were associated with an increased proportion of gallstones.